1996
DOI: 10.1016/0039-9140(95)01753-4
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration and analysis of gold from cyanide solutions with the use of a microcolumn packed with the phosphine oxide Cyanex 921

Abstract: The phosphine oxide Cyanex 921 (tri-n-octylphosphine oxide) was found to be a very efficient extradant for gold from aurocyanide aqueous solutions. A system comprising a microcolumn packed with this new reagent was developed for the separation and enrichment of gold. Because of the high selectivity of the developed system it is possible to analyze gold in the presence of an excess of other metals and/or in high ionic strengh solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…[40][41][42] To verify the best conditions with regard to the formation of complexes, extraction and recovery metals, many studies have been performed to date. [43][44][45][46][47][48][49] Furthermore, numerous studies have reported the use of this compound as an alternative for the synthesis of nanoparticles, controlling and inhibiting their growth morphology. [50][51][52] Moreover, its use is widely known in preparing quantum dots of InP, CdSe and ZnO in a range of organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] To verify the best conditions with regard to the formation of complexes, extraction and recovery metals, many studies have been performed to date. [43][44][45][46][47][48][49] Furthermore, numerous studies have reported the use of this compound as an alternative for the synthesis of nanoparticles, controlling and inhibiting their growth morphology. [50][51][52] Moreover, its use is widely known in preparing quantum dots of InP, CdSe and ZnO in a range of organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TOPO is used as a co-chelator or a synergistic agent, which protects the chelate from external interaction by filling the unoccupied slots in the metal-ion coordination sphere [4,5]. To verify the best conditions for complex formation, extraction, and recovery of metals, many studies have been performed so far [3,[6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Though ion-exchange resins and solid-supported extractants, usually based on PS-DVB or certain methacrylates are cheap "working horses" [15][16][17][18][19][20][21][22][23][24][25], they sometimes suffer from insufficient selectivity or require special conditions such as pH or ionic strength of the solution, which are hard to realize starting from standard metal ion containing aqua regia solutions. A variety of different sorbents for the selective extraction of other metal ions such as lanthanides prepared by various metathesis polymerization-based techniques has already been described [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%